The Effect of Organizational Culture, Leadership Style and Job Satisfaction on Employee Performance at PT Pegadaian (Persero) In Kendari City - Pardju, Pardju (International Journal of Management and Education in Human Development, 2021)
The purpose of this study was to test and analyzed: 1) Effect of culture the organization is partial to the performance of employees. 2) The influence of style of leadership is partial to the performance of employees. 3) Effect of satisfaction work is partially against the performance of employees. The research design used is quantitative research. The population in this study is all employees of PT. There are 75 pawnshops in Kendari City, using saturated sampling. Data collection in the form of interviews and questionnaires. As for technique analysis s data using the model SmartPLS version 2.0. Results of the study show that:1) Cultural organizations impact significantly on the performance of employees. 2)The leadership style impact significantly on the performance of employees, and 3) satisfaction of work affect significantly on the performance of employees.